Results of Posterior Occipito-Cervical Decompression and Fusion in Case of Basilar Invagination: A Case Series. Issue 1 (April 2016) - Patel, Ankit
Introduction: The term "Craniovertebral Junction" includes bony and neuro-vascular structures from base of occiput to 2nd cervical vertebrae. The subject of CV junction anomalies is under discussion and evaluation for over a century. Several classical reviews have attempted to clarify a variety of complex associated issues. Despite the volumes of publications on the subject, it appears that the last word has not yet been said. Basilar invagination is the most common craniovertebral junction anomaly. Basilar invagination implies that the floor of the skull is indented by the upper cervical spine, & hence the tip of odontoid is more cephalad protruding into the foramen magnum which causes the compression of medulla and brainstem. There are two types of basilar invagination: primary invagination, which is congenital or developmental and more common, and secondary invagination, which is acquired mostly due to trauma. Primary invagination can be associated with occipito-atlantal fusion, hypoplasia of the atlas, a bifid posterior arch of the atlas, odontoid anomalies. In basilar invagination, all three parts of the occipital bone (basiocciput, exoccipital & squamousoccipital bone) are deformed. Material and Methods: Our study is short term prospective study. Study period extends from July 2012 to May 2015. Total 20 patients {male+female} of various age group {8 year to 65 year} with diagnosed cases of basilar invagination were taken for study purpose. Results: Clinical outcomes: 17 patients showed improvement in their symptoms or gait with improved mJOA score, RANAWAT's neurological class and NURICK'S functional scale. 2 patients did not show any signs of improvement. 1 patient who had severe basilar invagination with os odontoideum with kyphotic deformity expired on 3rd postoperative day due to respiratory insufficiency. 1 patient had wound related complication with opening of stitches and exposed implant which required excision of exposed implant and wound recovered by secondary healing. On long term follow up 1 patient had loosening of implant from occiput bone on X-ray but she had no any clinical symptoms. Rest of patients had no long term complications. Radiologically: Using Mcrae, chamberlain line and Ranawat index, all 19 patients had reduction of dens below foramen magnum. Bone graft fused in all 19 patients between 6 to 8 months. So all over mortality rate of our study was 5%. Conclusion: Basilar invagination anomalies are commonly occurring but rarely diagnosed anomalies. Developmental and congenital anomalies are more common than traumatic events. As per our prospective study excellent to good short term results can be achieved with acceptable safety but it needs further long term follow up in larger series to confirm good long term results. Good results depend on proper patient selection, good surgical skill, proper use of implants and post operative care.